Ghrelin enhances tubular magnesium absorption in the kidney - Nie, Mingzhu; Zhang, Jing; Bal, Manjot; Duran, Claudia; An, Sung Wan; Zigman, Jeffrey M.; Baum, Michel; Hiremath, Chitkale; Marciano, Denise K.; Wolf, Matthias T. F. (Frontiers in Physiology, 2024)
Osteoporosis after bariatric surgery is an increasing health concern as the rate of bariatric surgery has risen. In animal studies mimicking bariatric procedures, bone disease, together with decreased serum levels of Ca2+, Mg2+ and the gastric hormone Ghrelin were described. Ghrelin regulates metabolism by binding to and activating the growth hormone secretagogue receptor (GHSR) which is also expressed in the kidney. As calcium and magnesium are key components of bone, we tested the hypothesis that Ghrelin-deficiency contributes to osteoporosis via reduced upregulation of the renal calcium channel TRPV5 and the heteromeric magnesium channel TRPM6/7. We expressed GHSR with TRPV5 or TRPM6/7 channel in HEK293 cells and treated them with purified Ghrelin. Whole-cell current density was analyzed by patch-clamp recording. Nephron-specific gene expression was performed by tubular microdissection followed by qPCR in wild-type (WT) mice, and immunofluorescent imaging of GHSR-eGFP mice. Tubular magnesium homeostasis was analyzed in GHSR-null and WT mice at baseline and after caloric restriction. After Ghrelin exposure, whole-cell current density did not change for TRPV5 but increased for TRPM6/7 in a dose-dependent fashion. Applying the Ghrelin-mimetic (D-Trp7, Ala8,D-Phe10)-α-MSH (6–11) amide without and with the GHSR antagonist (D-Lys3)-GHRP6, we confirmed the stimulatory role of Ghrelin towards TRPM6/7. As GHSR initiates downstream signaling via protein kinase A (PKA), we found that the PKA inhibitor H89 abrogated TRPM6/7 stimulation by Ghrelin. Similarly, transfected Gαs, but not the Gαs mutant Q227L, nor Gαi2, Gαq, or Gα13 upregulated TRPM6/7 current density. In microdissected TALs and DCTs similar levels of GHSR mRNA were detected. In contrast, TRPM6 mRNA was expressed in the DCT and also detected in the TAL at 25% expression compared to DCT. Immunofluorescent studies using reporter GHSR-eGFP mice showed a strong eGFP signal in the TAL but surprisingly displayed no eGFP signal in the DCT. In 3-, 6-, and 9-month-old GHSR-null and WT mice, baseline serum magnesium was not significantly different, but 24-h urinary magnesium excretion was elevated in 9-month-old GHSR-null mice. In calorically restricted GHSR-null mice, we detected excess urinary magnesium excretion and reduced serum magnesium levels compared to WT mice. The kidneys from calorically restricted WT mice showed upregulated gene expression of magnesiotropic genes Hnf1b, Cldn-16, Cldn-19, Fxyd-2b, and Parvalbumin compared to GHSR-null mice. Our in vitro studies show that Ghrelin stimulates TRPM6/7 via GHSR and Gαs-PKA signaling. The murine studies are consistent with Ghrelin-GHSR signaling inducing reduced urinary magnesium excretion, particularly in calorically restricted mice when Ghrelin levels are elevated. This effect may be mediated by Ghrelin-upregulation of TRPM6 in the TAL and/or upregulation of other magnesiotropic genes. We postulate that rising Ghrelin levels with hunger contribute to increased renal Mg2+ reabsorption to compensate for lack of enteral Mg2+ uptake.